Glucocorticoid receptor hypersensitivity enhances inflammatory signaling and inhibits cell cycle progression in porcine PBMCs - Li, Zhiwei; Hadlich, Frieder; Wimmers, Klaus; Murani, Eduard (Frontiers in Immunology, 2022)
The consequences of glucocorticoid receptor (GR) hypersensitivity during infection have so far received little attention. We previously discovered that a natural gain-of-function Ala610Val substitution in the porcine GR aggravates response of pigs to lipopolysaccharide (LPS)-induced endotoxemia, which can be alleviated by dexamethasone (DEX) pretreatment. In this work, we investigated the relevant molecular basis of these phenotypes by transcriptomic profiling of porcine peripheral blood mononuclear cells (PBMCs) carrying different GR genotypes, in unstimulated conditions or in response to DEX and/or LPS in vitro. The Val allele differentially regulated abundant genes in an additive-genetic manner. A subset of more than 200 genes was consistently affected by the substitution across treatments. This was associated with upregulation of genes related i.a. to endo-lysosomal system, lipid and protein catabolism, and immune terms including platelet activation, and antigen presentation, while downregulated genes were mainly involved in cell cycle regulation. Most importantly, the set of genes constitutively upregulated by Val includes members of the TLR4/LPS signaling pathway, such as LY96. Consequently, when exposing PBMCs to LPS treatment, the Val variant upregulated a panel of additional genes related to TLR4 and several other pattern recognition receptors, as well as cell death and lymphocyte signaling, ultimately amplifying the inflammatory responses. In contrast, when stimulated by DEX treatment, the Val allele orchestrated several genes involved in anti-inflammatory responses during infection. This study provides novel insights into the impact of GR hypersensitivity on the fate and function of immune cells, which may be useful for endotoxemia therapy.